(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Ideological and political education can be both facilitated and hindered by the current media landscape. Using a novel teaching concept in today’s modern media environment, English teaching, ideology, and politics can be linked to reaching a win-win situation in order to further promote ideological education. It is a ground-breaking topic to examine the role of English instruction in college ideological education in the age of new media.